2016
DOI: 10.1111/1755-5922.12163
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Reduces Circulating Osteoprogenitor Cells and T‐Cell RANKL Expression in Osteoporotic Women: Implications for the Bone–Vascular Axis

Abstract: SUMMARYAim: Circulating osteoprogenitors and receptor activator of nuclear factor kappa-B ligand (RANKL) expression in immune cells have been implicated in the pathogenesis of osteoporosis and vascular calcification. The role played by statin therapy in the bone-vascular axis is unknown. Methods: Twenty na€ ıve postmenopausal osteoporotic hypercholesterolemic women were treated with Atorvastatin 40 mg/day for 3 months. Gene expression analysis was performed to assess modification in osteoprotegerin (OPG)/RANK/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Uzzan et al found that statins showed a better action on cortical bone and positive effect on BMD in various sites, and there was a modest but statically significant favorable effect of statins on BMD; however, the reason was not understood 10. Molecular biology and genetics reveal that both vascular and osteoblast biology have a common pathway RANK/RANKL/OPG 48,49. With regard to this issue, there is growing interest concerning the possible mechanism and the impact of statins on bones on either the experimental or the clinical level.…”
Section: Discussionmentioning
confidence: 99%
“…Uzzan et al found that statins showed a better action on cortical bone and positive effect on BMD in various sites, and there was a modest but statically significant favorable effect of statins on BMD; however, the reason was not understood 10. Molecular biology and genetics reveal that both vascular and osteoblast biology have a common pathway RANK/RANKL/OPG 48,49. With regard to this issue, there is growing interest concerning the possible mechanism and the impact of statins on bones on either the experimental or the clinical level.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the percentage of myeloid OC+BAP+ cells was higher in peripheral blood and bone marrow of type 2 diabetic patients, and in diabetic carotid endarterectomy specimens, a higher degree of calcification and amounts of OC and BAP-expressing cells were detected in the α-smooth muscle actin-negative areas surrounding calcified nodules, where CD68+ macrophages colocalized (Fadini et al, 2011 ). The increased percentage of COPs in pathological conditions was evidenced also in other clinical studies and it is supposed to be “linked to the presence of vascular damage, such as arterial stiffness and aortic calcification” (Pal et al, 2010 ; Pirro et al, 2011 ; Rattazzi et al, 2016 ). However, in 2005, Eghbali-Fatourechi et al ( 2005 ) showed that the presence of a population of osteoblast-lineage cells circulating in physiological condition endowed with expression of markers of bone formation and markedly increasing during pubertal growth, thus representing a previously unknown component of bone formation process (Table 1 ).…”
Section: Endogenous Progenitor Cells In Bone Repair: Locally Residentmentioning
confidence: 73%
“…Statins can modulate the function of different immune cells, including T cells, and endothelial cells. 26 , 27 Many cell receptors and cytokines can be reduced by statins, such as MCH-II, P-selectin, and MCP-1. 28 In addition, statins exert direct antibacterial and antiviral effects.…”
Section: Discussionmentioning
confidence: 99%